Islamic Civil Society and Constitutionalism Issues in Indonesia: Observing the Expressions of the Banyumas Muslim Community in Responding to the Dynamics of State Problems in Post-Reformation - Khashogi, Luqman Rico; Humaidi, M. Wildan (International Journal of Social Science and Religion (IJSSR), 2023)
This research seeks to map out the expressions of the Banyumas Muslim community in responding to the dynamics of state problems in post-reformation with the Big Five theory (Openness, Conscientiousness, Extraversion, Agreeableness, and Neurotism). This research not only maps the potential involvement of Islamic civil society, but also contributes an important perspective as an effort to stabilize society and its various social groups. The method of collecting data was by distributing purposive questionnaires collecting 165 people. All of them consisted of various Islamic community organizations. The reliability used test-retest reliability, based on Friedman's theory with the lowest limitation of 0.90. The validity used direct validity, which is based on the development of the Big Five theory by Kathrin Ackermann, with moderate adjustments and concrete adaptations, thus it can be used operationally. The results of the study show that on the one hand, they have the character of extraversion (E) which has a more conservative attitude, encourages acceptance of hierarchy, and has more high trust in institutionalized matters. But on the other hand, they tend to be openness to experience (O) characters who have a critical attitude towards political, social values, norms and authority.